2004
DOI: 10.1002/jsfa.1944
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model of sugar diffusion from sugar beet tissue treated by pulsed electric field

Abstract: Extraction of sugar from sugar beet slices was studied following various pulsed electric field (PEF) treatments (intensities from 300 to 800 V cm −1 and number of pulses varying between 50 and 1000). Slices treated by PEF were immersed in water at ambient temperature at a liquid/solid ratio of 3. A significant increase in extraction yield was observed. This enhancement was due to permeabilisation of the cellular membrane and to the additional quantity of juice appearing on the surface of slices after PEF treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 12 publications
1
22
0
1
Order By: Relevance
“…It can be noted that effective electroporation of the red beet tissue at ambient temperature can be attained even at lower electric fields of 400-600 V/cm [89]. The PEF-assisted expression [15,49,77], aqueous extraction [23,24] and their combination [36] were studied for carrots. The material enhancement of the juice yield could be attained even at rather low voltage gradient of 360 V/cm [15].…”
Section: Other Roots and Tubersmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be noted that effective electroporation of the red beet tissue at ambient temperature can be attained even at lower electric fields of 400-600 V/cm [89]. The PEF-assisted expression [15,49,77], aqueous extraction [23,24] and their combination [36] were studied for carrots. The material enhancement of the juice yield could be attained even at rather low voltage gradient of 360 V/cm [15].…”
Section: Other Roots and Tubersmentioning
confidence: 99%
“…The PEF application has a large potential as an alternative to conventional thermal technology. Recently, the PEF-assisted pressing and aqueous extraction from sugar beets were intensively studied [14,16,21,23,24,28,45,46,62,93].…”
Section: Sugar Beetsmentioning
confidence: 99%
“…Previous studies have found that plant tissue disruption under PEF treatments can be achieved within 0.1 to 10 ms at electric field strengths between 0.5 to 5.0 kV/cm (Lebovka, Bazhal, & Vorobiev, 2001;Angersbach, Heinz, & Knorr, 2000). Significant membrane breakdown in potato and apple tissues has been observed when electric field strengths applied increased from 0.4 to 0.8 kV/cm (El-Belghiti, Rabhi, & Vorobiev, 2005). Under the conditions applied in the present study, it is suggested that membranes may be considered to exist in either of the two states, i.e.…”
Section: Water Mobility By Td-nmr Relaxometry In Pef-treated Carrot Smentioning
confidence: 63%
“…Fig. 9b shows the Arrhenius plots of the effective sugar diffusion coefficient D eff of PEF treated sugar beets from two independent experiments (Lebovka et al, 2007a;El-Belghiti et al, 2005). For example, PEF treatment conducted at E=0.1 kV/cm and t PEF = 1 s caused the reduction of the activation energy from ≈ 75 kJ/mol (untreated sample) to ≈ 21 kJ/mol, with the D eff values being always larger for PEF treated samples (Lebovka et al, 2007a).…”
Section: Effect Of Pef On Mass Transfer Rates During Extraction Procementioning
confidence: 97%